First in vitro and in vivo experiments with ultra high-dose rate oxygen ion radiotherapy - Celine Karle; Domenico I. Filosa; Mahdi Akbarpour; Nora Schuhmacher; Stephan Brons; Rainer Cee; Christian Schömers; Stefan Scheloske; Kristoffer Petersson; Thomas Haberer; Amir Abdollahi; Jürgen Debus; et al. (Physics and Imaging in Radiation Oncology, 2025)
Within this study, we demonstrated the feasibility of ultra-high dose rate (UHDR) oxygen ion irradiation at three different levels of biological complexity. The difference in oxygen consumption between UHDR and standard dose rates (SDR) was negligible in a protein-enriched saline solution. For the studied conditions of dose, dose rate and linear energy transfer (LET), UHDR irradiation showed comparable efficacy to SDR in pancreatic cancer cell killing in vitro, along with inducing a similar tumor growth delay in vivo. These findings emphasize the potential of high-LET UHDR irradiation and support further investigation of oxygen ions at UHDR.